The Impact of Audit Quality and Corporate Governance on Financial Segment Disclosure in Egypt - Engy Elsayed Abdelhak; Khaled Hussainey (International Journal of Financial Studies)
This paper examines the impact of audit quality and internal corporate governance mechanisms on segment disclosure. It uses manual content analysis to measure the levels of disclosure for a sample of Egyptian-listed companies from 2015 to 2023. It provides evidence that audit quality, joint audit, gender diversity, and board independence have a positive impact on the segment disclosure level. In contrast, audit opinion, foreign directors, and military background directors have a negative impact on the segment disclosure level in Egypt.